Blending Traditional and Digital Approaches in English Learning at MIN 1 Palembang: a Practical Overview - fitriani; Masagus Firdaus (EDUCATION JOURNAL OF INDONESIA, 2025)
This article explores the implementation of traditional and digital teaching methods in English language instruction at Madrasah Ibtidaiyah Negeri (MIN) 1 Palembang. The school applies two classroom models—digital and non-digital—to accommodate different student needs and infrastructure availability. In traditional classes, teachers rely on textbooks, oral practice, and paper-based activities. In contrast, digital classes incorporate multimedia tools such as PowerPoint, YouTube, and interactive online platforms like Quizizz and Wordwall. Through a qualitative descriptive approach, this article highlights how both teaching methods are applied, how they are blended, and how students and teachers experience these approaches in real classroom situations. The article concludes that combining traditional and digital methods can improve student engagement, support various learning styles, and enhance the overall quality of English language learning in primary education. Recommendations are also provided to help teachers and schools make the most of available resources. Keywords: English language teaching, Traditional methods, Digital learning, Blended learning